Commenters as a Threat to Journalism? How Comment Moderators Perceive the Role of the Audience. Issue 7 (8th August 2020) - Wolfgang, J. David; McConnell, Stephen; Blackburn, Hayley
Abstract: Journalists and commenters have struggled to negotiate the appropriate use of news forums. But research about perceptions of commenters has typically focused on journalists and not the comment moderators who specifically manage content. This study uses in-depth interviews with 13 U.S. news comment moderators to understand through a field theory analysis how moderators perceive commenters as possible threats to the profession and, potentially, help to develop quality commenting into a form of journalistic cultural capital.